The use of youtube as a social media platform in vocal learning for elementary school students at hardman music course - Suryani, Charoline Artha Dewi; Ismulyani, Latifah; Hidayatullah, Riyan (Mitra PGMI: Jurnal Kependidikan MI, 2025)
This study aims to explore the use of YouTube as a digital-based learning medium in vocal instruction for elementary school students at the Hardman Music Course. Employing a qualitative approach, data were collected through interviews with two students and one instructor. The findings reveal that YouTube is utilized as a source of backing tracks (e.g., Karaoke Piano channel) and independent learning materials (e.g., Vokal Plus channel by Indra Aziz), supporting students' vocal development both in class and at home. The vocal techniques taught include vocalizing exercises, diaphragmatic breathing, articulation, and mastery of vocal registers such as head voice, chest voice, falsetto, and belting. The learning process is strengthened by teacher-led gradual correction and evaluative feedback using students recorded performances. The integration of YouTube fosters flexibility, student autonomy, and engagement in learning, aligning with the digital habits of today’s elementary learners. However, challenges such as students’ shyness and lack of confidence remain prominent, requiring teachers to adopt supportive and psychologically responsive teaching strategies. This study underscores the potential of social media to enhance motivation, accessibility, and learning independence among elementary students in non-formal music education settings.